Drivers of Business Social Responsibity in Lesotho SMMEs: Evidence from Small Manufacturing Firms in the Thetsane Industrial Estate in Maseru - Dr Francis Okyere, (IJRDO - Journal of Business Management, 2019)
Given the significant role played by small, medium and micro enterprises (SMMEs) in socio-economic development, this paper seeks to gain an insight into their business social responsibility (BSR) practices. The objective of this paper is to examine why SMMEs in Lesotho engage in BSR activities. The concept of BSR is still new to Lesotho SMMEs, probably because of the dearth of empirical research on the subject. Furthermore, the neglect of SMMEs BSR practices in not justified considering the important role they play in economies. This study examined the reasons why SMMEs in Thetsane industrial estate in Maseru, Lesotho engage in social responsibility practices. The study focused on 10 textile manufacturing SMMEs in Thetsane industrial estate in the Maseru District of Lesotho. By using qualitative approach, the questionnaire based interview tested reasons why SMMEs engage in BSR. The results revealed that the quest to achieve good company image, increased satisfied customers as well as motivated and satisfied employees (which may lead to increased productivity) are the dominant drivers of small businesses engagement in BSR. These findings and implications are discussed in this study.